Pengaruh Kedisiplinan terhadap Hasil Belajar Siswa pada Mata Pelajaran PPKn di Kelas X SMA Negeri 14 Medan - Nainggolan, Titin Irawati; Habeahan, Sampitmo (AS-SABIQUN, 2024)
The aim of this research is to determine the influence of learning discipline in relation to their achievement in Civics lessons at level X SMA Negeri 14 Medan. This research was carried out at SMA Negeri 14 Medan which is located on Jalan Siswa Timur Ujung, Gang Darmo, Medan Denai District, Medan City. The type of research carried out by the author is qualitative research which is correlational in nature and applies quantitative descriptive research methods. This quantitative study includes two variables, namely x which describes the level of discipline and y which shows student learning outcomes. The population of this study includes all class In this research, the tools used in data collection include questionnaires, observation and documentation. In this research, the data applied uses quantitative statistical methods by calculating product moment. Research findings indicate that discipline has a minimal impact, namely 24.3%, on the learning achievement of class X students at SMA Negeri 14 Medan. This can be proven by calculating the correlation coefficient between variable x and variable y, which produces a calculated r value of 0.493. If this value is compared with the rtable value at a significance level of 5% then n=40, then rcount is obtained which is the specified criterion. If the rcount value is greater than rtable (rcount > rtable) or 0.493 > 0.312, then the conclusion will be drawn that it can have a significant influence between disciplines and the learning outcomes of level X students at SMA Negeri 14 Medan.